Follow the Wise Studies in Jewish History and Culture in Honor of Lee I. Levine - Adler, Yonatan; Amit, David; Barag, Dan; Baumgarten, Albert; Cohen, Shaye; Demsky, Aaron; Freyne, Sean; Gruen, Erich; Hachlili, Rachel; Horst, Pieter; Irshai, Oded; Kalmin, Richard; et al. (Penn State University Press, 2021)
In 1961, when Lee Israel Levine graduated from both Columbia College in New York, majoring in philosophy, and Jewish Theological Seminary, majoring in Talmud, this accomplishment was only a precursor to the brilliant career that would follow. While researching his Columbia University dissertation in Jerusalem, Levine established close ties with members of the Institute of Archaeology at Hebrew University and Prof. Yigael Yadin, who recognized the need for an interdisciplinary approach that would give graduate archaeology students a solid base in Jewish history and rabbinic sources to supplement their archaeological training. Levine accepted Yadin's invitation to return to Israel after graduation to teach at the Institute of Archaeology and later was granted a joint appointment in the Institute of Archaeology and the Department of Jewish History. In 1985, he was promoted to the rank of Full Professor, and since 2003, he has held the Rev.